2014
DOI: 10.1177/1040638714559597
|View full text |Cite
|
Sign up to set email alerts
|

Pathology and diagnosis of proliferative and ulcerative dermatitis associated with Tunga penetrans infestation in cattle

Abstract: Tunga penetrans is the smallest biting flea known. In cattle, infestation by T. penetrans (tungiasis) typically affects the skin of the distal legs, udder, prepuce, and perianal area. A detailed clinical and pathologic description of bovine tungiasis, together with electron microscopy and molecular diagnostics to establish the identity of the parasite are described. Ninety percent of the cows and heifers and 80% of the bulls in a herd in northwest Argentina had proliferative and ulcerative skin lesions affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…In addition to proper animal husbandry practices, which are often difficult to implement in impoverished villages with very poor infrastructure, treatment protocols for infected animals would be highly beneficial. However, there is no approved drug treatment for animal tungiasis [ 36 , 37 ]. Studies aimed at improving this situation are very scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to proper animal husbandry practices, which are often difficult to implement in impoverished villages with very poor infrastructure, treatment protocols for infected animals would be highly beneficial. However, there is no approved drug treatment for animal tungiasis [ 36 , 37 ]. Studies aimed at improving this situation are very scarce.…”
Section: Introductionmentioning
confidence: 99%
“…This was also observed in this study, possibly related to the histological incidence of the cut surface of the parasite. Similarly, previous studies have shown the histopathological features of T penetrans in humans 20 and in cattle, 19 as well as scarcely in monkeys 12 and gorillas; 11 however, there are no studies with regard to the pathological and parasitological features of T penetrans in southern brown howler monkeys.…”
Section: Discussionmentioning
confidence: 96%
“…In the southern brown howler monkey 2, the clinical condition was severe at the clinical examination, and the primate died shortly after arrival, allowing to perform a more detailed pathological and parasitological investigation, with identification of T penetrans as the etiological agent. Microscopically, the presence of the head, exoskeleton, hypodermal layer, striated muscles, tracheal rings, digestive tract, female reproductive tract, and developing eggs, as observed in the southern brown howler monkey 2, are histological features of T penetrans infestation in humans 16,17,18 and in cattle 19 . Some structures, such as the exoskeleton, hypodermal layer, tracheae, digestive tract, and developing eggs, are more frequently found than the striated muscles and the head in human biopsies 16 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations